Evaluating case studies of community-oriented integrated care. Issue 4 (4th July 2018) - Thomas, Paul; Sachar, Amrit; Papanikitas, Andrew; While, Alison; Brophy, Chris; Manning, Chris; Mills, Cliff; Ruprah-Shah, Baljeet; Millington-Sanders, Catherine; Morris, David; Kelley Patterson, Deirdre; Hill, Diana; et al.
Abstract: This paper summarises a ten-year conversation within London Journal of Primary Care about the nature of community-oriented integrated care (COIC) and how to develop and evaluate it. COIC means integration of efforts for combined disease-treatment and health-enhancement at local, community level. COIC is similar to the World Health Organisation concept of a Community-Based Coordinating Hub – both require a local geographic area where different organisations align their activities for whole system integration and develop local communities for health. COIC is a necessary part of an integrated system for health and care because it enables multiple insights into 'wicked problems', and multiple services to integrate their activities for people with complex conditions, at the same time helping everyone to collaborate for the health of the local population. The conversation concludes seven aspects of COIC that warrant further attention.